Decisão judicial em controle de constitucionalidade das normas tributárias: análise sob o enfoque da teoria da linguagem - Silva, Renata Elaine (2008)
The present work aims at analyzing the judicial decisions in control of constitutionality of the tax norms. The analysis will be elaborated from the theory of how the judicial decision is processed, decision premises, limit and construction of the applier of the law of the of the concrete norm of judicial decision. Afterwards, through the very decisions uttered in constitutionality control from Federal Supreme Court, pragmatic will be analyzed. The whole theory and practical development in the work will be accomplished in agreement with the Theory of the Language as construction of the Law in its syntactic, semantic and pragmatic aspects